O ELITISMO DEMOCRÁTICO EM ROBERT DAHL - Tiago Valenciano (Universidade do Oeste Paulista, 2010)
The objective is to check the texts "A preface to democratic theory" (1989) e "A critique of the ruling elite model" (1970), of Robert Alan Dahl (1915), notions about democracy and pluralism in politics. The focus is directed to the organized political groups that are in constant struggle toachieve power. In relation to this dispute questioned: in a democratic system, which is the notion of competition policy and so that these groups face off to win the election, according to the ideas of Dahl? For this, we will develop the work into three parts: the democract thinking Dahl (1989), the criticisms made by Dahl in relation to the organizational model of political elites (1970) and the conclusion, highlighting the main points of the author.